(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate postoperative nausea & vomiting (PONV) with and without metoclopramide with opioid use for control of pain. Study Design: Interventional comparative study Place and Duration of Study: This study was carried out at KAH, Bisha, Saudi Arabia for period of 3 months 18th July 2014 to 17th October 2014. Patients and Methods: Fifty patients were included and divided into Group A & B. Group A was given inj. Fentanyl 1.5mg/kg intra-operatively and Inj. Pethidine 1.5mg/kg post-operatively to control pain. Group B was given inj. Metoclopramide 0.15 mg/kg intra-operatively and same dose postoperatively in addition to Inj. Fentanyl and Pethidine. Results: In Group A, 10 (40%) female patients and 02 (8%) male patients developed PONV while in Group B only one (4%) female patient developed PONV. Conclusion: PONV is reduced when anti-emetics are used along with opioids for pain control. Inj. Metoclopramide, an anti-dopaminergic prokinetic, was found to give better results as its antiemetic action is considered.